Serological Evidence of Henipavirus Exposure in Cattle, Goats and Pigs in Bangladesh - Chowdhury, Sukanta (PLoS Negl Trop Dis, 2014)
BACKGROUND: Nipah virus (NiV) is an emerging disease that causes severe encephalitis and respiratory illness in humans. Pigs were identified as an intermediate host for NiV transmission in Malaysia. In Bangladesh, NiV has caused recognized human outbreaks since 2001 and three outbreak investigations identified an epidemiological association between close contact with sick or dead animals and human illness. METHODOLOGY: We examined cattle and goats reared around Pteropus bat roosts in human NiV outbreak areas. We also tested pig sera collected under another study focused on Japanese encephalitis. PRINCIPAL FINDINGS: We detected antibodies against NiV glycoprotein in 26 (6.5%) cattle, 17 (4.3%) goats and 138 (44.2%) pigs by a Luminex-based multiplexed microsphere assay; however, these antibodies did not neutralize NiV. Cattle and goats with NiVsG antibodies were more likely to have a history of feeding on fruits partially eaten by bats or birds (PR = 3.1, 95% CI 1.6–5.7) and drinking palmyra palm juice (PR = 3.9, 95% CI 1.5–10.2). CONCLUSIONS: This difference in test results may be due to the exposure of animals to one or more novel viruses with antigenic similarity to NiV. Further research may identify a novel organism of public health importance.